2012
DOI: 10.5198/jtlu.v5i3.266
|View full text |Cite
|
Sign up to set email alerts
|

How built environment affects travel behavior: A comparative analysis of the connections between land use and vehicle miles traveled in US cities

Abstract: Mixed findings have been reported in previous research regarding the impact of built environment on travel behavior-i.e., statistically and practically significant effects found in a number of empirical studies and insignificant correlations shown in many other studies. It is not clear why the estimated impact is stronger or weaker in certain urban areas and how effective a proposed land use change/policy will be in changing certain travel behavior. This knowledge gap has made it difficult for decision makers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(104 citation statements)
references
References 28 publications
3
92
0
Order By: Relevance
“…And it is usually quantified by distance to the central business district (CBD). Many researchers confirm that the location of residence has a significant influence on VMT and the influence is always negative [40][41][42].…”
Section: The Impacts Of Built Environment On Car Ownership and Usementioning
confidence: 99%
“…And it is usually quantified by distance to the central business district (CBD). Many researchers confirm that the location of residence has a significant influence on VMT and the influence is always negative [40][41][42].…”
Section: The Impacts Of Built Environment On Car Ownership and Usementioning
confidence: 99%
“…The net impact on overall VMT patterns will depend on the aggregation across the effects on individual travel dimensions. However, most earlier studies on the effect of BE measures on travel, while considering residential self-selection, focus directly (and solely) on the effect on vehicle miles of travel (see Zhang et al, 2012, Salon et al, 2012, which are but a few recent examples). There have also been studies that consider residential self-selection and focus on BE effects on specific travel dimensions, such as auto ownership, vehicle type, trip frequencies, bicycle ownership, activity durations, and mode choice, though these have been relatively few and have focused on each dimension individually (see Bhat andKrizek, 2012 for detailed reviews).…”
Section: The Current Paper In the Context Of Earlier Studiesmentioning
confidence: 99%
“…Indeed, the literature on the subject is now vast and growing rapidly, with a substantial amount of quantitative and qualitative research having been undertaken in the past decade (see, for example, Bhat and Guo, 2007, Transportation Research Board, 2009, Ewing and Cervero, 2012, Pinjari et al, 2011, Zhang et al, 2012, Handy and Krizek, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Residents of mixed-use urban areas were seen to make shorter journeys. Zhang et al (2012) also suggested that compact, mixed-use developments are effective in reducing vehicles miles traveled (VMT) per person through shorter journeys.…”
Section: Accessibilitymentioning
confidence: 99%